Bylem garbusem u Polanskiego-- - Priwieziencew, Eugeniusz, 1946- (Poznan : Atena, 1991)
These are recollections of a Polish film actor who worked under Polanski.
Keywords: Priwieziencew, Eugeniusz, -- 1946-; Polanski, Roman; Motion picture actors and actresses -- Poland -- Biography